2016
DOI: 10.4172/2155-6113.1000602
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Mistrust, Conspiracy Theories and Attitudes towards HIV Testing Among African Americans

Abstract: Background: With respect to the HIV epidemic, research has shown that health behaviors are affected by a number of attitudinal factors such as cultural mistrust, medical mistrust and conspiracy beliefs. While it is clear that these variables have a deleterious effect on health behaviors, the literature fails to explore how these factors uniquely influence and predict an individual's attitudes and overall willingness to receive HIV testing. Furthermore, cognitive factors such as the need for cognitive closure h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
2
15
0
2
Order By: Relevance
“…Several correlational studies have shown that belief in health‐related conspiracy theories is associated with the choice to use contraception and practice safe sex. Specifically, one conspiracy theory alleges that birth control is a form of genocide against Africans and African Americans (see Ball, ; Ford, Wallace, Newman, Lee, & William, ). This conspiracy theory is believed widely in both the United States and South Africa (Hogg et al, ; Nattrass, ).…”
Section: Definitionsmentioning
confidence: 99%
“…Several correlational studies have shown that belief in health‐related conspiracy theories is associated with the choice to use contraception and practice safe sex. Specifically, one conspiracy theory alleges that birth control is a form of genocide against Africans and African Americans (see Ball, ; Ford, Wallace, Newman, Lee, & William, ). This conspiracy theory is believed widely in both the United States and South Africa (Hogg et al, ; Nattrass, ).…”
Section: Definitionsmentioning
confidence: 99%
“…Among the most common conspiracy theories in this population are those related to themes of "benign neglect," which are predicted by generalized mistrust and having been a victim of police harassment, without correlation to political alignment (Parsons et al, 1999;Simmons & Parsons, 2005). The intersection of epistemic mistrust and BCT within the African American community has been explored more specifically within Human Immunodeficiency Virus (HIV)/Acquired Immunodeficiency Syndrome (AIDS)-related conspiracy theories such as beliefs that HIV is a manmade virus created and spread by the Central Intelligence Agency or that treatments are either withheld from the African American community or cause rather than treat AIDS (Ball, Lawson, & Alim, 2013). A survey of 500 US African Americans found that over half believed that AIDS information is withheld from the public and that a cure for AIDS exists but is being withheld from the poor, with nearly half believing that HIV is a man-made virus and that those taking new antiviral medications are "human guinea pigs for the government" (Bogart & Thorburn, 2005).…”
Section: Pierre 621mentioning
confidence: 99%
“…as if a symptom of pathology, the community's modern mistrust in medicine may stem from lived experiences such as the 1932-1979 Tuskegee Syphilis Study if not others that predate it (Ball, Lawson, & Alim, 2013;Heller, 2015). "Cultural paranoia" has therefore been reframed as "cultural mistrust" (Whaley, 2001), defined as a "racism reaction" characterized by "a tendency to distrust Whites based upon a legacy of direct or vicarious exposure to racism or unfair treatment by Whites" (Thompson et al, 2004, p. 210).…”
Section: Pierre 621mentioning
confidence: 99%
“…Indeed, independent of BCT, it has been found that African American mistrust of white people is negatively correlated with knowledge about HIV transmission (Klonoff & Landrine, 1997) and that general medical mistrust is associated with lower medication adherence with HIV medications (Dale et al, 2016). Although mistrust within the African American community has been historically labeled "cultural paranoia" as if a symptom of pathology, the community's modern mistrust in medicine may stem from lived experiences such as the 1932-1979 Tuskegee Syphilis Study if not others that predate it (Ball, Lawson, & Alim, 2013;Heller, 2015). "Cultural paranoia" has therefore been reframed as "cultural mistrust" (Whaley, 2001), defined as a "racism reaction" characterized by "a tendency to distrust Whites based upon a legacy of direct or vicarious exposure to racism or unfair treatment by Whites" (Thompson et al, 2004, p. 210).…”
Section: Cultural Mistrust Trust Violations and Conspiracy Theoriesmentioning
confidence: 99%